Small shoes, great strides : how three brave girls opened doors to school equality - Nelson, Vaunda Micheaux (Carolrhoda Books, 2023)
"A powerful true story about three Black girls who courageously integrated a New Orleans school on November 14, 1960, told by award-winning author Vaunda Micheaux Nelson"--